2000
DOI: 10.2139/ssrn.248818
|View full text |Cite
|
Sign up to set email alerts
|

Recent Amendments to the Korean Commercial Code and Their Effects on International Competition

Abstract: Korea has undergone a dramatic transformation in recent years. In an effort to revamp Korean corporations, the Korean government made sweeping reforms to Korea's Commercial Code (sang-bup) three times in the past four yearsin 1995, 1998, and 1999.' These newly amended provisions have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…Of the fund managers surveyed, 95 per cent keep the shares in their portfolios for less than one year, which reflects the fact that Korea's financial environment is changeable and many fund managers and organisations are seeking short-term profits rather than longterm profits and dividends. This is comparable with Kim (2000), who stated that individual shareholders in Korea held shares for an average of 1.2 months in 1999. 5 The respondents indicated that their investment is mainly in the following sectors: information and telecommunication, semi-conductors, electronics and IT.…”
Section: Sample Selection and Research Methodologiessupporting
confidence: 78%
“…Of the fund managers surveyed, 95 per cent keep the shares in their portfolios for less than one year, which reflects the fact that Korea's financial environment is changeable and many fund managers and organisations are seeking short-term profits rather than longterm profits and dividends. This is comparable with Kim (2000), who stated that individual shareholders in Korea held shares for an average of 1.2 months in 1999. 5 The respondents indicated that their investment is mainly in the following sectors: information and telecommunication, semi-conductors, electronics and IT.…”
Section: Sample Selection and Research Methodologiessupporting
confidence: 78%
“…Opaqueness, rather than transparency, was a standard modus operandi, allowing for effective concealment of tunneling from regulators and minority shareholders. Chaebols have contributed significantly to a wide range of structural weaknesses which were exposed by the 1997 financial crisis (e.g., Kim, 2000).…”
Section: South Korean Chaebolsmentioning
confidence: 99%
“…Kim (2000) provided a thorough review of South Korea's Commercial Code (henceforth KCC) and outlined a number of judicial issues related to the functioning of South Korean directors that allowed for widespread tunneling within cheabols prior to implementation of the major legal revisions of 1998 and 1999. He showed that under South Korean jurisdiction the concepts of duty of care and the duty of loyalty were not clearly distinguished, and, instead, the ''duty of diligence as a good custodian'' was the principle guiding directors' obligations to their firm.…”
Section: Tunneling Within South Korean Chaebolsmentioning
confidence: 99%
See 2 more Smart Citations